Stakeholders’ Perception on Influence of Covid-19 Pandemic On Activities of Private Senior Secondary Schools in Ilorin Metropolis - Olaifa, A. Sunday; Ismail, A. Ramoni; Atanda, O. Olaide (Kashere Journal of Education, 2022)
The study investigated the stakeholders’ perception on influence of Covid-19 Pandemic on activities of private senior secondary schools in Ilorin Metropolis, Kwara State. Descriptive survey design was adopted using questionnaire as an instrument for data collection. The population of the study was the stakeholders of the private schools at senior secondary level of education in Ilorin Metropolis. The study made use of 30 School Administrators, 120 Teachers and 150 Students of 30 selected private senior secondary schools in all three local government areas that constitute Ilorin Metropolis. The researcher’s self-designed questionnaire was used to obtain information from the 300 respondents. Questionnaire titled: “Covid-19 Pandemic and School Activities Questionnaire (CPSAQ) was used to elicit information. The reliability of the instrument was carried out using test re-test method with reliability index of 0. 849 while the research hypotheses formulated for the study were tested using t-test at 0.05 level of significance. The results of the analysis revealed that there are no significant differences in the perceptions of teachers and students on the influence of Covid-19 on school activities of private senior secondary schools in Ilorin Metropolis, Kwara State. Although School administrators viewed the influence of Covid-19 on school activities of private senior secondary schools differently. The study recommends that teachers need to prepared themselves to explore the full range of opportunities that remote learning offers through online platforms, social media, Television, radio etc. to ensure continuity of learning during an unforeseen situation that may affect traditional classroom activities. Also school authority should diversify alternative methods through which co- curricular and extracurricular activities of the school can be taken care of in case of an emergency outbreak like Covid-19.